2021
DOI: 10.1002/adma.202006613
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Stability of Non‐Noble‐Metal M–N–C Catalysts for Proton‐Exchange‐Membrane Fuel Cells through M–N Bond Length and Coordination Regulation

Abstract: An effective and universal strategy is developed to enhance the stability of the non‐noble‐metal M–Nx/C catalyst in proton exchange membrane fuel cells (PEMFCs) by improving the bonding strength between metal ions and chelating polymers, i.e., poly(acrylic acid) (PAA) homopolymer and poly(acrylic acid–maleic acid) (P(AA‐MA)) copolymer with different AA/MA ratios. Mössbauer spectroscopy and X‐ray absorption spectroscopy (XAS) reveal that the optimal P(AA‐MA)–Fe–N catalyst with a higher Fe3+–polymer binding cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 117 publications
(78 citation statements)
references
References 62 publications
(43 reference statements)
1
67
0
Order By: Relevance
“…Usually, longer bond lengths are conducive to maintaining the structural integrity of the catalyst. [55] Wavelet-transform (WT) EXAFS is prone to distinguishing the backscattering atoms because of its high-resolution in both k space and R space. [56] The WT of Fe-PpPD-800 is shown in Figure 3c, the intensity maximum is observed at k = 5 Å −1 , which is very close to FePc and can be designated as the contribution of FeN bonds.…”
Section: Resultsmentioning
confidence: 99%
“…Usually, longer bond lengths are conducive to maintaining the structural integrity of the catalyst. [55] Wavelet-transform (WT) EXAFS is prone to distinguishing the backscattering atoms because of its high-resolution in both k space and R space. [56] The WT of Fe-PpPD-800 is shown in Figure 3c, the intensity maximum is observed at k = 5 Å −1 , which is very close to FePc and can be designated as the contribution of FeN bonds.…”
Section: Resultsmentioning
confidence: 99%
“…A mono-atomic catalyst has the characteristics of stability and high efficiency, which can be used in various batteries and electrochemical storage devices, can drive the research of a series of energy conversion and storage devices, and accelerate the exploration and development of green energy [94]. The highly stable non-precious metal M-NX/C singleatom catalyst has application prospects in proton-exchange-membrane fuel cells and promotes the development of the transportation industry [95].…”
Section: Batteriesmentioning
confidence: 99%
“…Li and co-workers regulated the Fe−N coordination and bond length by tuning the binding constant between metal ions and chelating polymers in the catalyst precursor. 69 As shown in Figure 4a and b, XAS and 57 Fe Mossbauer spectroscopy analyses revealed that the higher binding constant resulted in a longer Fe−N bond. The optimized catalyst with longer Fe−N bonds exhibited outstanding stability in a H 2 -air fuel cell, with near 100% current retention for the first 37 h at 0.55 V (Figure 4c).…”
mentioning
confidence: 93%